If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2b-3+5b=6
We move all terms to the left:
-2b-3+5b-(6)=0
We add all the numbers together, and all the variables
3b-9=0
We move all terms containing b to the left, all other terms to the right
3b=9
b=9/3
b=3
| n5− 1=3 | | 10+(1)/(3)y=1 | | -27=–3p+15–3p | | -18=4q+-10 | | 4.3=v+6 | | -8=4q+-10 | | (4x+12)=(5x-4) | | z+33/9=7 | | k/7+20=26 | | -53=10+-9d | | 4x-2(x-6)=-10 | | 5x2+25=75 | | 5(s+4)=90 | | -4(w+10)=20 | | 5b+18+3b=82 | | 25x+26x-5=180 | | 2.25x+0.50x-10=12 | | 3p+3=3p+2 | | d/10+64=71 | | -3(g+20)=-18 | | 3p=3=3p=2 | | 14x+8=-48 | | 20x−2x−3x−11x+2x=18 | | 20x+24=64 | | 17-2j=11 | | 6k-3k+k=4 | | 15+2x=39+x | | 7(x+38)=280 | | 10+3k=19 | | 3(p−7)=6 | | |n-10|=16 | | z/7-6=-3 |